Metabolomic Analysis of Pisang Ambon Lumut at Post-Harvest Stage as a Rapid-Analysis Method of Ripening Fruit - Amelinda Pratiwi; Shelina Lauren; Vivi Hasna Fatinah; Zahra Novyani; Amelia Maulidina; Intan Farhani (Universitas Sebelas Maret (UNS), 2024)
Banana is a fruit that is much favored by the people of Indonesia and is one type of climacteric fruit, namely a fruit that can still experience ripening after harvesting. The sensory and nutritional composition of Ambon Lumut bananas can be influenced by their level of ripeness. FTIR fingerprinting metabolite analysis on Ambon Lumut bananas can be an immediate method to assess fruit quality. Therefore the purpose of this study is to identify the ideal time for banana ripening in order to preserve the quality of Ambon Lumut bananas by analyzing the fingerprints of various metabolite chemicals in the bananas after harvest. This study focused on the post-harvest analysis of the metabolites of Pisang Ambon Lumut at storage times of days 0 (C), 4 (P4), 8 (P8), and 12 (P12) with the metabolomic approach using FTIR. The results of the FTIR spectrum were extracted using Excel, normalized the wave number data, then chemometric analysis was performed using The Unscrambler software. Based on the results of Principal Component Analysis (PCA), there are several metabolites that characterize each banana sample, including fat in banana C; in P4 bananas, protein, and dietary fiber were detected; in P8 bananas, disaccharide, aromatic, and phenyl compounds were detected; and in P12 bananas, disaccharide compounds were detected. The results of the metabolomic analysis showed that the banana samples stored on the 4th day (P4) had the most optimum nutritional composition compared to other samples.